Didactic strategies to strengthen chemical language in education - Elizeth Mayrene Flores Hinostroza; Derling Jose Mendoza Velazco; Lorena Soledad Revilla; Karina Maribel Castillo Pinos (Journal of Counseling, Education and Society, 2022)
The objective of the research article presented below was to propose activities that would strengthen the students of the educational institution "Unidad del Milenio Manuel J." through training activities in the teaching, understanding, and adequate application of the language of chemistry. Street" in the city of Cuenca - Ecuador (MJC), immersed in a feasible project, using the descriptive field design, the population was constituted with 25 students of unified general high school, the observation technique and the questionnaire were used for the collection of information, then with the results found in the diagnosis a proposal was built to give answers to the proposed objectives. In addition to the above, activities were developed to strengthen the chemical sciences, increasing the ability of chemical language, interacting with chemical symbols in a correct way. With all this, innovative and participatory processes were sought to help students assimilate and appropriate the required knowledge, providing answers to their needs for learning chemical language, assuming scientific attitudes, typical of the areas of knowledge, such as being critical and autonomous in their own learning.